Cost Analysis of Endoscopic Conduit Harvesting Technique Using a Non-Sealed System for Coronary Artery Bypass Surgery. Issue 4 (July 2022) - Rosati, Fabrizio; Pervez, Mohammad Bin; Palacios, Camila Mayorga; Tomasi, Cesare; Mastroiacovo, Giorgio; Pirola, Sergio; Bonomi, Alice; Polvani, Gianluca; Bisleri, Gianluigi
Objective: Endoscopic vessel harvest (EVH) is evolving as the standard of care for coronary artery bypass grafting. However, the increase in upfront equipment-related costs has resulted in reluctance of uptake globally. We investigated the costs involving a non-sealed technique for EVH versus open vessel harvesting techniques (OVH) for both the greater saphenous vein and radial artery with a 6-month follow-up.Methods: From September 2016 to December 2018, 226 patients underwent OVH while 251 patients underwent EVH using a reusable non-sealed system and a single-use radiofrequency sealing system. Cumulative costs for OVH versus EVH were calculated as a summation of total operative and in-hospital stay costs. Costs related to harvest site complication management were also analyzed for up to 6 months.Results: Total operative costs were greater in the EVH group (Can2, 283.70 [Can1, 377.60 to 4, 183.50] vs Can1, 742.40 [Can998.50 to 3, 628.10], P < 0.001). Total length of stay was significantly shorter for the EVH group (5.9 [4 to 43] days vs 6.8 [4 to 55] days, P = 0.018). Cumulative costs were comparable at the end of the hospitalization period (EVH, Can6, 534.70 [Can2, 076.50 to 33, 087.70] vs OVH, Can6, 112.50 [Can3, 322.30 to 45, 503.50], P = 0.06). After discharge, harvest site–related complications occurred more frequently in the OVH group (27% vs 4.4%, P < 0.001), resulting in increased use of antibiotics (2.2% vs 0.8%, P = 0.02) as well as more frequent requirement for home nursing assistance in the OVH group (5.7% vs 0.8%, P = 0.002) at 6 months of follow-up.Conclusions: Cumulative costs did not show a statistical difference between OVH and EVH, with higher intraoperative costs for EVH being offset by higher harvest site management costs in the OVH group.